Evaluasi Efektivitas Kebijakan Work from Home terhadap Produktivitas Karyawan: Sebuah Studi Literatur - Euis Susanti; Dwi Astuti (GLOBAL SCIENTS PUBLISHER, 2025)
Abstract This study aims to evaluate the effectiveness of work from home (WFH) policies on employee productivity through a literature study approach. The COVID-19 pandemic has encouraged many companies to implement WFH as a new work strategy. This study examines 15 national and international journals in the 2019–2024 period that discuss the impact of WFH on productivity. The results of the study indicate that the effectiveness of WFH is influenced by several main factors, namely time management skills, technology support, organizational communication, and work-life balance. Although WFH provides flexibility, challenges such as social isolation and lack of direct supervision can reduce performance. This study recommends a combination of WFH and WFO (hybrid working) as the optimal solution. This study is important for HR managers in designing adaptive work policies in the future.